Siderophores: More than Stealing Iron - Judith Behnsen (American Society for Microbiology, 2016)
ABSTRACT Siderophores are small molecular iron chelators that are produced by microbes and whose most notable function is to sequester iron from the host and provide this essential metal nutrient to microbes. Recent studies have proposed additional, noncanonical roles for siderophores, including the acquisition of noniron metals and modulation of host functions. Recently, Holden et al. (V. I. Holden, P. Breen, S. Houle, C. M. Dozois, and M. A. Bachman, mBio 7:e01397-16, 2016, http://dx.doi.org/10.1128/mBio.01397-16) showed that siderophores secreted by Klebsiella pneumoniae during lung infection induce stabilization of the transcription factor HIF-1α, increase the expression of proinflammatory cytokines in the lung, and promote dissemination of K. pneumoniae to the spleen. Thus, their study demonstrated novel roles for siderophores in vivo, beyond iron sequestration. The interaction of siderophores with host cells further promotes the pathogenicity of K. pneumoniae and is likely relevant for other pathogens that also secrete siderophores in the host.